2019
DOI: 10.1186/s13020-019-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B: dynamic change in Traditional Chinese Medicine syndrome by dynamic network biomarkers

Abstract: BackgroundIn traditional Chinese medicine (TCM) clinical practice, TCM syndromes help to understand human homeostasis and guide individualized treatment. However, the TCM syndrome changes with disease progression, of which the scientific basis and mechanism remain unclear.MethodsTo demonstrate the underlying mechanism of dynamic changes in the TCM syndrome, we applied a dynamic network biomarker (DNB) algorithm to obtain the DNBs of changes in the TCM syndrome, based on the transcriptomic data of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Among the four cytokines, IL-4 and INF- γ showed statistical significance not only between the syndromes but also among the syndromes and healthy group, and these two cytokines may have potential as the biochemical indicators of the two TCM-syndromes. In addition, the results also demonstrated that almost all the cytokines were expressed much higher in LDSDS than in SSDHS, and this suggested that the immune response may be more intense in LDSDS than in SSDHS, and this result was also consistent with Lu et al (2019) [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Among the four cytokines, IL-4 and INF- γ showed statistical significance not only between the syndromes but also among the syndromes and healthy group, and these two cytokines may have potential as the biochemical indicators of the two TCM-syndromes. In addition, the results also demonstrated that almost all the cytokines were expressed much higher in LDSDS than in SSDHS, and this suggested that the immune response may be more intense in LDSDS than in SSDHS, and this result was also consistent with Lu et al (2019) [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
“…[ 26 ]. TCM syndrome plays an important role in TCM treatment, and the same disease with different TCM syndromes in western medicine could receive different treatments in TCM [ 11 ]. However, due to the fact that TCM-syndrome is overrelying on experience, this greatly limits its application worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have observed relations between recurrent pregnancy loss and FXII deficiency. The results showed that plasminogen and coagulation FXII were significantly expressed during the development of TCM syndrome from liver-gallbladder dampness-heat syndrome to liver-kidney yin-deficiency syndrome ( Lu et al, 2019 ). The contact activation system is initiated upon binding of FXII to negatively charged surfaces such as artificial chemicals like kaolin or ellagic acid, or of natural origin, such as polyphosphates, 2 collagen, 3 and nucleic acids ( Visser et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to TCM theory and clinical experience, CHB patients are likely to be infected with a damp heat virus, which can lead to liver and gallbladder dysfunction, such as liver depression and spleen deficiency, which in turn causes disease (8,9). TCM has a number of advantages in the treatment of CHB.…”
Section: Discussionmentioning
confidence: 99%